Modeling growing confluent tissues using a lattice Boltzmann method: interface stability and fluctuations - Killeen,A; Bertrand,T; Lee,CF (Physical Review Research, 2023)
Tissue growth underpins a wide array of biological and developmental processes, and numerical modeling of growing systems has been shown to be a useful tool for understanding these processes. However, the phenomena that can be captured are often limited by the size of systems that can be modeled. Here, we address this limitation by introducing a lattice Boltzmann method (LBM) for a growing system that is able to efficiently model hydrodynamic length scales. The model incorporates a bounce-back approach to describing the growing front of a tissue, which we use to investigate the dynamics of the interface of growing model tissues. We find that the interface grows with scaling in agreement with the Kardar-Parisi-Zhang (KPZ) universality class when growth in the system is bulk driven. Interestingly, we also find the emergence of a previously unreported hydrodynamic instability when proliferation is restricted to the tissue edge. We then develop an analytical theory to show that the instability arises due to a coupling between the number of cells actively proliferating and the position of the interface.